Experiences of environmental services workers in a tertiary hospital in Asia during the COVID-19 pandemic: a qualitative study - Ng, Qin Xiang; Koh, Nicholas Ye Kai; Xin, Xiaohui; Zainal, Humairah; Tan, Jack Thian; Thumboo, Julian; Fong, Kok Yong (Frontiers in Public Health, 2023)
BACKGROUND: The Coronavirus Disease 2019 (COVID-19) pandemic has had a significant impact on all walks of life, in particular, environmental services workers in healthcare settings had higher workload, increased stress and greater susceptibility to COVID-19 infections during the pandemic. Despite extensive literature describing the impact of the pandemic on healthcare workers such as doctors and nurses, studies on the lived experiences of environmental services workers in healthcare settings are sparse and none has been conducted in the Asian context. This qualitative study thus aimed to examine the experiences of those who worked for a year of the COVID-19 pandemic. METHODS: A purposive sample of environmental services workers was recruited from a major tertiary hospital in Singapore. Semi-structured interviews were conducted in-person, lasting from 20 to 30 minutes, and included open-ended questions pertaining to five main domains: work experiences during COVID-19, training and education needs, resource and supplies availability, communication with management and other healthcare staff, and perceived stressors and support. These domains were identified based on team discussions and literature review. The interviews were recorded and transcribed for thematic analysis, as guided by Braun and Clarke. RESULTS: A total of 12 environmental services workers were interviewed. After the first seven interviews, no new themes emerged but an additional five interviews were done to ensure data saturation. Our analysis yielded three main themes and nine subthemes, including (1) practical and health concerns, (2) coping and resilience, and (3) occupational adaptations during the pandemic. Many expressed confidence in the preventive efficacy of proper PPE, infection control practice and COVID-19 vaccination in protecting them against COVID-19 and severe illness. Having prior experience with infectious disease outbreaks and previous training in infection control and prevention appeared to be useful as well for these workers. Despite the various challenges presented by the pandemic, they could still find meaning in their everyday work by positively impacting the wellbeing of patients and other healthcare workers in the hospital. CONCLUSIONS: Besides uncovering the concerns shared by these workers, we identified helpful coping strategies, resilience factors and certain occupational adaptations, which have implications for future pandemic planning and readiness.